Blood Profile of Tilapia (Oreochromis niloticus) Given Feed Mixed with Soursop Leaf Extract (Annona muricata L.) - Maryani, Maryani; Fadillah, Fauzan Ari; Yulintine, Yulintine; Rozik, Mohamad; Rosita, Rosita (Journal of Fish Health, 2025)
Efforts to combat disease in farmed fish are typically done using antibiotics. However, long-term use of antibiotics can lead to disease resistance and environmental pollution. One herbal extract with potential as an immunostimulant is the soursop plant (Annona muricata L.). This study aims to understand the hematology of tilapia (Oreochromis niloticus) that were fed a diet mixed with soursop leaf extract (Annona muricata L.). The study design included four treatments and three repetitions, comprising treatment A (control), treatment B (2.5 g/kg feed), treatment C (5 g/kg feed), and treatment D (7.5 g/kg feed). The results showed that feeding a diet mixed with soursop leaf extract at a concentration of 7.5 g/kg feed (treatment D) could influence the increase in hematocrit levels by 26.11%, hemoglobin levels by 7.11 g/dl, and total leukocytes by 4.41 x 104 cells/mm3, but did not affect the total erythrocytes of tilapia.